2014
DOI: 10.1111/cas.12463
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐135a acts as a putative tumor suppressor by directly targeting very low density lipoprotein receptor in human gallbladder cancer

Abstract: The precise functions and mechanisms of microRNAs (miR) in gallbladder cancer (GBC) remain elusive. In this study, we found that miR-135a-5p expression is often dampened and correlated with neoplasm histologic grade in GBC. MicroRNA-135a-5p introduction clearly inhibited GBC cell proliferation in vitro and in vivo. Moreover, very low density lipoprotein receptor (VLDLR), which is often upregulated in GBC tissues, was identified as a direct functional target of miR-135a-5p. Furthermore, the p38 MAPK pathway was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 20 publications
4
66
0
Order By: Relevance
“…Thus, it might be a better resolution to establish more-accurate prognostic gene signatures by using a combination of different types of transcripts (24). A growing volume of literature has demonstrated that noncoding RNAs, predominantly miRNAs, could serve as potential biomarkers of gallbladder cancer (3,25). Given the fact that lncRNAs are more abundantly expressed in mammalian cells, it is plausible to speculate that lncRNAs, once regarded as "transcriptional noise," may be potential prognostic indicators in gallbladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it might be a better resolution to establish more-accurate prognostic gene signatures by using a combination of different types of transcripts (24). A growing volume of literature has demonstrated that noncoding RNAs, predominantly miRNAs, could serve as potential biomarkers of gallbladder cancer (3,25). Given the fact that lncRNAs are more abundantly expressed in mammalian cells, it is plausible to speculate that lncRNAs, once regarded as "transcriptional noise," may be potential prognostic indicators in gallbladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the transfection of a miRNA135a-5p mimetic inhibited proliferation and colony formation of GBC cells by G1/S phase cell-cycle block; lentivirus-mediated overexpression of miRNA-135a signiicantly reduced the proliferation of GBC cells. In addition, xenografts from miRNA-135a-infected cells in nude mice were signiicantly smaller compared to controls [9]. These evidences suggested the oncosuppressive role of this miRNA in GBC.…”
Section: Onco-suppressor Mirnas In Gallbladder Cancermentioning
confidence: 86%
“…Its levels have been found to be signiicantly downregulated in GBC tissues and were correlated with the histological grade of the tumors [9]. Furthermore, the transfection of a miRNA135a-5p mimetic inhibited proliferation and colony formation of GBC cells by G1/S phase cell-cycle block; lentivirus-mediated overexpression of miRNA-135a signiicantly reduced the proliferation of GBC cells.…”
Section: Onco-suppressor Mirnas In Gallbladder Cancermentioning
confidence: 99%
“…miRNA expression profiling has been performed by large-scale microarray analysis in GBC tissues or cells in several studies (26,(46)(47)(48). Numerous miRNAs exhibit expression changes, with some miRNAs being upregulated, but most being downregulated in GBC cells and tissues.…”
Section: Micrornas and Gbcsmentioning
confidence: 99%
“…These data provide proof that miR-135a-5p may inhibit the proliferation of GBC cells in vitro and in vivo. Furthermore, it was demonstrated that miR-135a exhibited this function through directly binding the 3'-UTR of very low-density lipoprotein receptor, thus resulting in activation of the p38 mitogen-activated protein kinase pathway (47).…”
Section: Tumor Suppressor Micrornasmentioning
confidence: 99%